39 CAN BEHAVIOURAL CHANGE INTERVENTIONS IMPROVE SELF-EFFICACY AND EXERCISE ADHERENCE AMONG PEOPLE WITH PARKINSON'S? A SYSTEMATIC REVIEW. (25th October 2022) - Ahern, L; Timmons, S; Lamb, S; McCullagh, R
Abstract: Background: People with Parkinson's (PwP) lead sedentary lifestyles compared to healthy peers. Personal influences including low self-efficacy and poor outcome expectation appear to predict exercise adherence more accurately than disease severity. The purpose of this review is to identify successful behavioural-change interventions that promote self-efficacy and exercise adherence among PwP. Methods: Databases including EBSCO, Medline, CINAHL, Web of Science, PubMed, Embase, Scopus, Google Scholar and Cochrane Library were searched from inception to 2020. Interventional studies including a behavioural-change intervention were included. Title, abstract and full-text screening was conducted by two independent reviewers. The Cochrane Risk of Bias Tool and Robins-I were used to assess the Risk of Bias. Data was extracted by two independent reviewers. The outcomes of interest were self-efficacy, quality of life, physical function, and exercise adherence. A narrative synthesis was completed and mapped to the Theoretical Domains Framework, to produce practice-orientated outcomes. Results: Seventeen studies (n=1319) were included. Risk of bias was generally moderate. A multicomponent behavioural-change intervention encompassing education, behavioural strategies and support groups appeared to improve quality of life, physical function, and exercise adherence in PwP. No intervention improved self-efficacy. Self-monitoring, goal setting, social supports, feedback, self-managements skills and action planning improved long-term adherence. Conclusion: No intervention changed self-efficacy. However, it appears that a multicomponent intervention is essential to improve exercise adherence. Trials directly comparing different intervention types and adequate follow-up periods are limited, preventing a conclusive finding of the most effective behavioural-change intervention to promote exercise adherence among PwP.